Vitamin D Levels In Children with Bronchial Asthma - Somashekar, A. R. (J Clin Diagn Res, 2014)
Introduction: Bronchial Asthma is a common chronic inflammatory disorder of the airways in childhood. Vitamin-D, required for bone mineralization, is also a potent immune system regulator having a potential role in various allergic diseases. This study was undertaken to determine the difference in serum levels of Vitamin-D in asthmatic children and to determine the association between vitamin-D and asthma in children. Materials and Methods: This cross-sectional study included 88 (44 asthmatic children and 44 healthy controls) children aged between 5 and 13 y. Serum 25-hydroxy vitamin-D levels were determined and compared between the two groups. The association between vitamin-D levels and lung function was studied in the asthmatic children. Results: Serum vitamin-D level was significantly lower in asthmatic children than in control group and in the asthmatic group, vitamin-D levels had a significant positive correlation with FEV1% and FEV1/FVC%. Conclusion: Vitamin-D deficiency is highly prevalent in asthmatic children and is associated with airway limitation.